Integrated Framework for Inclusive Town Planning Using Fuzzy Analytic Hierarchy Method for a Semi Urban Town - Pratibha Bhadane; Radhika Menon; R. K. Jain; Deepa Joshi; Aboli A. Ravikar (Salehan Institute of Higher Education, 2022)
Planning is a continuous process and must incorporate a regular evaluation of implementation and further revision for effective and efficient utility for the betterment of society through modification of the planning standards. Development plans for cities / towns are criticized for being rigid and static, having little regard for investment planning efforts, and taking a very long time in the process of formulation and approval. In depth analysis and review of the existing situation, covering the demographic, economic, financial, infrastructure, physical, environmental, and institutional aspects, is important so as to identify the strengths and weaknesses in the city overall development. In the present study, an attempt has been made to thoroughly review the existing planning standards adopted for the preparation and implementation of development plans in India, especially in Maharashtra. Since the development plan's objectives are not measurable, this study will use the Fuzzy Analytic Hierarchy Process (AHP) to assess their level of performance. For the purpose of identifying the various viewpoints of various stakeholders, field surveys and questionnaire surveys were conducted. This application can be used as an objective evaluation tool for planners and policy makers to improve planning practices and provide necessary knowledge for revising plans. The results indicated the importance of criteria from the pre-planning, preparation, and implementation stages of DP. These results were used for two semi-urban towns in Maharashtra regions and could also be used by planning engineers for further development of planning standards. Doi: 10.28991/CEJ-2022-08-12-07 Full Text: PDF